The relationship between resilience and the intensity of social media use with psychological well-being of Gen-Z students - Fina Nur Fitriana; Fildzah Malahati (Jurnal Psikologi Tabularasa, 2024)
ABSTRACTIn recent years, there has been a strong emphasis on mental health, particularly among Generation Z students. Generation Z students are highly vulnerable to the negative effects of social media norms and expectations on their mental health. The purpose of this research is to examine how the mental health of Gen Z students is influenced by their level of social media use and resilience. This study employs a quantitative method with a correlational approach using multiple linear regression analysis. The respondents in this study consisted of 210 Gen Z college students aged 18-24 years, selected using accidental sampling techniques. Data collection was carried out using an online questionnaire through Google Forms on social media, which included a psychological well-being scale, a resilience scale, and a social media usage intensity scale. The reliability of the psychological well-being scale was 0.909, the resilience scale was 0.951, and the social media usage intensity scale was 0.831. The analysis results show that psychological well-being is significantly influenced by the combined effects of resilience and social media usage intensity, p <.001.ABSTRACTDalam beberapa tahun terakhir, ada penekanan kuat pada kesehatan mental, terutama di kalangan siswa dari Generasi Z. Siswa Generasi Z sangat rentan terhadap efek negatif dari norma dan ekspektasi media sosial pada kesehatan mental mereka. Tujuan dari riset ini adalah untuk melihat bagaimana kesehatan mental siswa Gen Z dipengaruhi oleh tingkat penggunaan dan resiliensi media sosial mereka. Metode kuantitatif berdasarkan pendekatan korelasional memakai analisis regresi linier berganda dipakai dalam riset ini. Responden pada penelitian ini berjumlah 210 orang mahasiswa Gen-Z dalam rentang usia 18-24 tahun dengan menggunakan teknik accidental sampling. Pengumpulan data dilakukan menggunakan kuesioner secara online melalui google form di sosial media yang terdiri dari skala kesejahteraan psikologis, skala resiliensi, dan skala intensitas penggunaan media sosial. Reliabilitas pada skala kesejahteraan psikologis sebesar 0,909, pada skala resiliensi sebesar 0,951, dan pada skala intensitas penggunaan media sosial sebesar 0,831. Hasil analisis menunjukkan bahwa kesejahteraan psikologis dipengaruhi secara signifikan oleh efek gabungan dari resiliensi dan intensitas penggunaan media sosial, p <.001.